Supplementation with nutritional additives and organic minerals on the performance of newly‑weaned Nellore calves on pasture - Palma, André Soligo Vizeu de; Barra, Camila Neri; Herling, Valdo Rodrigues; Gomide, Catarina Abdalla; Saran Netto, Arlindo (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the performance of newly‑weaned Nellore calves in response to supplementation with additives and organic minerals in protein mineral salt, in Urochloa brizantha 'Marandu' pasture, in the dry season. One hundred and twelve calves aged between 7–8 months and with 252±24 kg were used. The animals were divided into pastures under rotational stocking and received the following treatments: protein mineral salt (control); and protein mineral salt with minerals in organic form, with monensin, or with functional oils. For each grazing cycle, supplement intake, weight gain, and efficiency were calculated; blood samples for analysis of minerals were collected; and carcass ultrasound was made. The intake of the treatment with monensin was lower than that of the other ones (0.47 kg per day); the intakes of the control (0.82 kg per day) and the oil (0.8 kg per day) treatments were similar; and the intake of the treatment with organic minerals was higher than that of the others (0.92 kg per day). Differences among treatments were not observed for weight gain (0.123 kg per day) and for efficiency (0.161). Ribeye area (46.81 cm2) and fat thickness (0.77 mm) did not differ significantly among treatments. The addition of monensin decreases supplement intake, which can mean lower protein ingestion and limited animal performance.